Cerebellar hemisphere herniation in the neck: Case report of a very rare complication following a posterior fossa craniectomy. (2016) - Caruso, Riccardo; Pesce, Alessandro; Piccione, Emanuele; Marrocco, Luigi; Wierzbicki, Venceslao
Highlights: Cerebellar herniation following a craniectomy to the posterior fossa is a rare complication. Surgery was necessary to push the cerebellum back inside and plastic surgery to the bone was carried out. Possible causes were discussed. Abstract: This article presents a very rare late complication of surgery to the posterior fossa involving a craniectomy: cerebellar hemisphere herniation in the neck, through the craniectomy site. Here we also analyse the possible causes of such complication.